EPIDEMIOLOGY OF LOWER LIMB INJURY IN GAELIC FOOTBALL AND HURLING. Issue 7 (11th March 2014) - O'Malley, E; Murphy, J; Gissane, C; Blake, C
Abstract : Background: Gaelic football (GF) and hurling (H) are multi-directional, high velocity, contact sports. Elevated physical demands are thought to cause an increased rate of injury in the lower limb. Objective: To examine the incidence and describe lower limb injury in both Gaelic Football and hurling (2008–2011). Design: Four-year prospective epidemiological study. Setting: 25 Gaelic football teams and 21 hurling teams who compete at inter-county level participated. All data were anonymous. Ethical approval was received by the University College Dublin Human Research Ethics Committee. Participants: Adult male Gaelic football (n=841) and hurling (n=696) players were included. Interventions: Injury definitions comply with international best practice guidelines and consensus statements. Main outcome measurements: Lower Limb injury (LLI) characteristics, exposure information and player demographics were collected via an online platform. Injury rates are expressed as number of injuries per 1000 hours. Severity is expressed as days lost from sport. Percentages were calculated from available totals. Results: There were a total of 654 football and 560 hurling LLIs recorded. Match-play LLIs had a higher incidence in both codes (GF:29.8/1000 hrs, H:37.6/1000 hrs) than training LLIs (GF:2.4/1000 hrs, H:2.1/1000 hrs). LLIs caused a median of 16 days timeloss from Gaelic football and 14 days timeloss from hurling. When broken down by body-region, the thigh was the most commonly injured area (GF:42.0%, H:32.1%) followed by knee (GF:16.1%, H:19.3%). Hamstring injury was most prevalent (GF:29.1%; H:23.6%). Hamstring injuries caused a median of 20 days timeloss from football, 21 days lost in hurling. Muscle was the most commonly injured tissue (GF:51.2%, H:46.4%). The most common mechanism of LLI was sprinting (GF:32.1%, H:34.1%). Conclusions: This study provides new specific lower limb injury epidemiological information and is the first step towards injury prevention in two sports native to Ireland.